Removal of endocrine disrupting chemicals using low pressure reverse osmosis membrane - Abd. Razak, Azri Rasyidi (2009)
Endocrine disrupting chemicals (EDCs) are one of the major focuses of contaminants in current environmental issues, as they can cause adverse health effects on animals and human, particularly to endocrine function. The objective of this study was to remove a specific group of EDCs (i.e molecular weight range 228 to 288 g/mol) using low pressure reverse osmosis membrane (LPROM). A multi-layer thin-film composite of aromatic polyamide (ES20) membrane and a C10-T cross flow module of LPROM manufactured by Nitto Denko Company was used in this study. The effects of operating parameters, i.e. pH, operating pressure, concentration and temperature were observed using a design of experiment based on MINITABTM software. The analysis of results was conducted by factorial analysis (FA) and response surface analysis (RSA). It was found that LPROM has been effectively applied to remove pentachlorophenol (PCP) (more than 83%), 17ÃŸ-estradiol (more than 87%) and bisphenol-A (BPA) (more than 87%). For permeate flux, both PCP and 17ÃŸ-estradiol tests produce excellent flux rate; i.e. 23.8 L/m2.h and 22.9 L/m2.h, respectively. For BPA, the permeate flux produced was slightly lower (19.1 L/m2.h) due to its physical-chemical properties effect at various levels of the recovery rate. In this study, the percentage of rejection was increased with the increased of pH and concentration of compounds. The flux was observed to increase with the increase of operating pressure. This study also investigated the interaction effects between operating parameters involved. In addition, statistical models were developed to represent the performance of LPROM under two response parameters, i.e. percentage of EDCs rejection and permeate flux. Statistical models were then validated using One-Factor-At-a-Time (OFAT) design of experiments and comparisons were made to better understand the trend of EDCs rejection and permeate flux.